Effects of ACK and KAG Teachings in Sexual Behaviour Choices of Students in Selected Universities in Nairobi County, Kenya - Rotich, Marseline Cherono; Gecaga, Margaret; Gitome, Josephine (International Journal of Humanity and Social Sciences, 2023)
Purpose: This study sought to understand how the ACK and KAG sexuality teachings shaped the sexual behaviour choices of students in selected universities in Nairobi, Kenya. Methodology: The study utilized a mixed research design, incorporating both quantitative and qualitative methods. Quantitative data were gathered through a questionnaire, focusing on numerical analysis. The research covered three universities, employing probability sampling to select 334 participants proportionately. Additionally, qualitative insights were obtained through in-depth interviews and focus group discussions with 42 knowledgeable respondents, ensuring a comprehensive understanding of the research objectives. Findings: Descriptive statistics revealed that cohabiting, internet sex, and browsing porn were the most frequently observed behaviors, while heterosexual encounters scored the lowest. Principal component analysis identified two major clusters of negative sexuality: internet sex and cohabitation, and extreme sex. Internet sex and cohabitation accounted for 42% of all variance, while extreme sex accounted for 20%. T-test results indicated a significant effect of Protestant teachings on sexual behavior choices. While Protestant teachings explained a small proportion of the variance in these behaviors, they had a significant effect, suggesting a moderate relationship between these teachings and sexual behavior choices. Unique Contribution to Theory, Practice and Policy: Knowledge gleaned from this exercise would contribute to availing prompt well-intentioned information on how Christian beliefs can be enhanced to fight negative sexuality